2018
DOI: 10.1371/journal.pone.0191080
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals significant metabolic alterations in eri-silkworm (Samia cynthia ricini) haemolymph in response to 1-deoxynojirimycin

Abstract: Samia cynthia ricini (Lepidoptera: Saturniidae) is an important commercial silk-producing insect; however, in contrast to the silkworm, mulberry leaves are toxic to this insect because the leaves contain the component 1-deoxynojirimycin (DNJ). A transcriptomic analysis of eri-silkworm haemolymph was conducted to examine the genes related to different metabolic pathways and to elucidate the molecular mechanism underlying eri-silkworm haemolymph responses to DNJ. Eight hundred sixty-five differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…Previously, the differential genes of key enzymes involved in the energy metabolism were gathered from transcriptional profiling. 27 Combined with the metabolomic results, six genes were confirmed by RT-qPCR. Total RNA (1 μg) was reversely transcribed following the protocol of PrimeScript RT reagent Kit with gDNA Eraser (Perfect Real Time; Takara, China) and the qPCR amplification was carried out using TB Green® Fast qPCR Mix (Takara) in the CFX96 Touch™ System (Bio-Rad, USA).The relative transcriptional analysis of target genes was carried out according to the 2 −44Ct method.…”
Section: Extraction Of Rna and Rt-qpcrmentioning
confidence: 88%
See 1 more Smart Citation
“…Previously, the differential genes of key enzymes involved in the energy metabolism were gathered from transcriptional profiling. 27 Combined with the metabolomic results, six genes were confirmed by RT-qPCR. Total RNA (1 μg) was reversely transcribed following the protocol of PrimeScript RT reagent Kit with gDNA Eraser (Perfect Real Time; Takara, China) and the qPCR amplification was carried out using TB Green® Fast qPCR Mix (Takara) in the CFX96 Touch™ System (Bio-Rad, USA).The relative transcriptional analysis of target genes was carried out according to the 2 −44Ct method.…”
Section: Extraction Of Rna and Rt-qpcrmentioning
confidence: 88%
“…Previously, the differential genes of key enzymes involved in the energy metabolism were gathered from transcriptional profiling 27 . Combined with the metabolomic results, six genes were confirmed by RT‐qPCR.…”
Section: Methodsmentioning
confidence: 95%
“…The hierarchical clustering analysis suggested that most of the genes were up-regulated form 12 to 24 h after the validamycin treatment and were then down-regulated by 36 h. In Stenocoris furcifera, a comparative transcriptome analysis under three different insecticide-treatment conditions revealed that genes related to GST, P450s, ABC transporters and Hsps were up-regulated (Zhou et al, 2018). Zhang et al (2018) revealed that 577 DEGs were up-regulated and 288 DEGs were downregulated in Samia cynthia ricini after being treated with 1-deoxynojirimycin, and these genes were involved mainly in energy metabolism, glycometabolism and lipid metabolism (Zhang et al, 2018). Thus, the host might up-regulate the expression levels of these genes to defend against infiltration by exogenous entities.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome sequencing was performed on fifth‐instar larval hemolymph of S. c. ricini using the Illumina sequencing method (Beijing Novogene Bioinformatics Technology, Beijing, China) to obtain the S. c. ricini transcriptome database (Zhang et al, 2018). ScFerLCH was identified from the data set by TBLASTN.…”
Section: Methodsmentioning
confidence: 99%